Potensi dan Karakterisasi Bakteri Alami Pencernaan Ayam Broiler Pedaging (Gallus gallus domesticus L.) Sebagai Kandidat Probiotik Pakan Ayam Broiler - Adelia Febriyossa; - Nurmiati; - Periadnadi (Jurnal Biologi Universitas Andalas, 2013)
A study about potential and characterization of native bacteria of intestinebroiler (Gallus gallus domesticus L.) as probiotic candidate of a broiler poultry product were conducted from December 2012 to March 2013 at Microbiology Laboratory, Department of Biology, Andalas University, Padang. This study aimed to obtainbacterial isolates and to describe morphological characters of each isolate of native bacteria as probiotic candidate for thebroiler.This study used an experimental method and analyzed descriptively. The results showed that rough material of intestine consisted of fermentative bacteria (57x107cfu/g), amylolitic (118x107cfu/g), cellulolytic (63x107cfu/g) and proteolytic bacteria (52x107cfu/g). Two isolates were potensial probioticcandidates; amylolytic bacteria and cellulolytic bacteria. The characteristics both probiotic candidates were gram negative, non-sporulating, positive catalase and motile.Keywords: Gallus gallus domesticus, intestine bacteria, characterization